Bioprospecting and mechanistic insights of Trichoderma spp. for suppression of Ganoderma-induced basal stem rot in oil palm - Amrutha Lakshmi, M.; Indraja, M.; Singh, Udai B.; Subanna, A. R. N. S.; Challa, G. K; Mawar, Ritu; Dauda, W. P. (Frontiers in Nutrition, 2025)
PurposeBasal stem rot (BSR), with Ganoderma spp. as the principal causative agent, is an important oil palm disease, leading to significant stand loss and reduced yield potential. The use of antagonistic fungi, particularly Trichoderma spp., offers a sustainable approach to disease suppression through hyperparasitism, antibiosis, and rhizosphere competence. However, strain-dependent variability in antagonistic potential necessitates the selection of the most efficacious isolates for integrated BSR management. Here we show that T. afroharzianum exhibits superior antagonism against Ganoderma spp., in dual culture, inverted plate assay as well as cellfiltrate assays.MethodsFrom 50 Trichoderma isolates screened, 12 highly mycoparasitic strains (>80% Ganoderma suppression) were selected. To enhance applicability under field conditions, the selected strains were further evaluated against co-occurring soil-borne pathogens commonly associated with oil palm decline.ResultsT. afroharzianum exhibited hydrolytic enzyme secretion (chitinase, cellulase, and pectinase), solubilized key macronutrients, and suppressed multiple soil-borne phytopathogens including Rhizoctonia solani, R. bataticola, Fusarium solani, Lasiodeplodia theobromae Colletotrichum gleosporoides and Curvularia lunata. A tailored Trichoderma consortium achieved 61.94% disease suppression, reduced foliar and bole severity by 48.59 and 20.22%, respectively, and increased plant height (47.59 ± 2.52 cm) and shoot fresh weight (15.83 ± 0.80 g).Implications/conclusionThese findings establish T. afroharzianum as a promising biocontrol agent for BSR suppression through multiple mechanisms, including competitive exclusion and pathogen inhibition. The results support its potential for field deployment as part of an integrated, climate-resilient disease management strategy in oil palm cultivation.